Deep Dynamics - Nils Gottfries; Glenn Mickelsson; Karolina Stadin (Center for Economic Studies and Ifo Institute (CESifo), 2021)
How do firms adjust their output, inventories, employment and capital in response to demandsideshocks? To understand this, we estimate a reduced-form model using firm-level panel dataand we construct a theoretical model that can match the estimated impulse-response functions.A combination of convex adjustment costs and implementation lags explains input adjustmentvery well. Although inputs adjust slowly, production responds quickly to the demand shock andthis adjustment is explained by a combination of increasing returns and increased utilization ofthe production factors. To avoid stock-outs, firms increase their inventories when demandincreases.
Keywords: E22; E23; E24; E32; 330; production function; productivity; Solow residual; labor hoarding; effort; organizational capital; capacity; returns to scale; markup; inventory investment